2017
DOI: 10.1021/acsphotonics.7b00550
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Directional Emission from Monolayer WSe2 Integrated onto a Multiresonant Silicon-Based Photonic Structure

Abstract: Two-dimensional transition-metal dichalcogenides such as WSe 2 show great promise as versatile atomic-scale light sources for on-chip applications due to their advanced optoelectronic properties and compatibility with a silicon photonics platform. However, the sub-nanometer thickness of such active materials limits their emission efficiency. Hence, new approaches to simultaneously enhance the emission and control its directionality are required. Here, we demonstrate enhanced and directional emission from a WSe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 46 publications
0
43
0
Order By: Relevance
“…The discovery of single photon emitters (SPEs) in 2D materials has stimulated an intensive research effort, aimed at the exploitation of such sources for quantum photonics 10 as well as at the understanding of their physical origin. In the last years, SPEs have been reported on TMDs monolayers at cryogenic temperatures [11][12][13][14][15] and on layered hexagonal boron nitride at room temperature 16 . The origin of SPEs has been attributed to either presence of defects in the crystalline structure of the crystals 16,17 or bandgap modulation of the material due to local bending of the material itself, which naturally occurs on bubbles or wrinkles 18 .…”
mentioning
confidence: 99%
“…The discovery of single photon emitters (SPEs) in 2D materials has stimulated an intensive research effort, aimed at the exploitation of such sources for quantum photonics 10 as well as at the understanding of their physical origin. In the last years, SPEs have been reported on TMDs monolayers at cryogenic temperatures [11][12][13][14][15] and on layered hexagonal boron nitride at room temperature 16 . The origin of SPEs has been attributed to either presence of defects in the crystalline structure of the crystals 16,17 or bandgap modulation of the material due to local bending of the material itself, which naturally occurs on bubbles or wrinkles 18 .…”
mentioning
confidence: 99%
“…Besides changing the optical properties of Mie resonators intrinsically, active tuning may also be realized via coupling with 2D materials. Neshev et al have theoretically demonstrated the PL modulation of 2D materials based on the directional emission caused by Mie resonators [26]. Recently, the first experimental work has been done, in which a forward-to-backward emission ratio of 20 was realized because of the interaction between MoS 2 monolayer and Mie resonators [27].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the anomalous dispersion of periodically patterned structures enables beam steering in quantum emitters via near-field coupling of optical resonances. Owing to recent advances in monolayer transition metal chalcogenides with a direct band gap, theoretical and experimental research has explored 1D periodic grooves [10], two-dimensional (2D) photonic crystals [11,12], and hyperbolic metamaterials [13][14][15][16][17]. For example, Zhang et al reported unidirectional radiation with a narrow divergence angle from monolayer MoS 2 by exploiting Fano resonance in 2D freestanding photonic crystal slabs [11].…”
Section: Introductionmentioning
confidence: 99%